The Patrick O'Brian Muster book persons, animals, ships and cannon in the Aubrey-Maturin sea novels - Brown, Anthony Gary (McFarland & Co., 2006)
"Now in its second edition, this expanded work catalogs every person, animal, ship and cannon mentioned by name in the 21 books of Patrick O'Brian's series on the maritime adventures of Jack Aubrey and Stephen Maturin"--Provided by publisher.
Originally published: Persons, animals, ships and cannon in the Aubery-Maturin sea novels of Patrick O'Brian. Jefferson, N.C. : McFarland, 1999. With new foreword.
Includes bibliographical references and index -- "Now in its second edition, this expanded work catalogs every person, animal, ship and cannon mentioned by name in the 21 books of Patrick O'Brian's series on the maritime adventures of Jack Aubrey and Stephen Maturin"--Provided by publisher.
Erscheint: April 2006
Keywords: O'Brian, Patrick -- 1914-2000 -- Aubrey/Maturin novels; O'Brian, Patrick -- 1914-2000 -- Dictionaries; O'Brian, Patrick -- 1914-2000 -- Characters -- Dictionaries; O'Brian, Patrick <1914-2000> -- Aubrey/Maturin novels; O'Brian, Patrick -- 1914-2000; Maturin, Stephen (Fictitious character) -- Dictionaries; Aubrey, Jack (Fictitious character) -- Dictionaries; Characters and characteristics in literature -- Dictionaries; Naval art and science in literature -- Dictionaries; Historical fiction, English -- Dictionaries; Ships in literature -- Dictionaries; Ordnance -- Dictionaries; Wörterbuch